Population Ecology and Natural diet of Banded Leg Swimming Crab Charybdis annulata (Fabricius, 1798) at Ao Yang Bay, Chanthaburi Province - Kunsook, Chutapa; Nakeim, Sorasak; Surawut, Saowapha; Aektasang, Arisa (YRU Journal of Science and Technology, 2022)
Population ecology and natural diet of banded leg swimming crab Charybdis annulata (Fabricius, 1798) was carried out covered both dry and wet season at Ao Yang Bay, Chanthaburi Province on 2021. The result found that 126 samples of C. annulata. Sex ratio was 1 : 0.58. The abundance of crab was highest in station 2 (coral reef with seaweed Sargassum sp.) (51.59%) in contrast with station 5 (rocky shore with seaweed Gelidium sp.) had not found abundance of C. annulata. Carapace range distribution was highest 51-60 mm. The average carapace width was 53.66 ± 8.15 mm. The relationship between carapace width and weight was W = 0.0013CW2.5565. Study of natural diet of crab was studied by using frequency of occurrence method The result showed that the diet were fish (29.67%), organic matter (20.64%), seaweed (17.12%), crustacean (14.73%), sand (12.46%), plastic (5.13%) and mollusc (0.25%). The result also showed that sex and season was influenced to natural diet of this crab (p<0.05) while the relationship between abundance of crab and ecological factor was no correlated (p>0.05). The result from this research is not only found the role of C. annulata to Ao Yang Ecosystem but also know the impaction of pollutions to this crab. Therefore, related agency should be cooperated for this urgently solutions.